MHD Oscillatory Rotation Flow With Radiation Effects Along a Porous Medium Bounded by Two Vertical Porous Plates Under the Influence of Hall Current And Heat Absorption With Chemical Reaction - R. Karthikeyan; R. Dinesh Kumar (International Journal of Mathematics And its Applications, 2019)
Magnetohydrodynamics oscillatory flow in between two vertical porous plates through porous medium in presence of hall current has been studied. One plate is kept stationary and other plate is kept as oscillating. The basic governing equations of the problem are transformed into a system of non dimensional differential equations. Effect of various parameters on velocity , temperature and concentration, skin friction and rate of heat and mass transfer were studied. The non dimensional parameters influences are discussed graphically using perturbation method.